Malaysia’s dilemma: the need for a new identity politics framework - Gunggut, Haijon; Thomas, Bibianah; Zaaba, Zuraidah; Jalil, Saiful Zizi (Faculty of Administrative Science and Policy Studies, 2023)
The Malaysian politics has been labelled communal politics and rightly so for one of the most dominant and enduring themes of politics in the country is about race. In such politics, most issues are framed within the compartment of race. This essentially is the political narrative in the country since its inception. However, recently many have argued for the transition towards non-communal based politics. This article seeks to explore the merits of non-communal politics and communal politics framed within the context of identity versus non-identity politics, arguing that while both have merits that cannot be ignored, both tend to have limitations. Extreme identity politics in term of racial identity tends to be divisive and confrontational while at the other extreme, complete avoidance of identity politics may ignore or sweep over real concerns such as marginalization, neglect, oppression, and discrimination. A more desirable alternative might be accepting identity politics as one of the many themes of politics promoting welfare of the people while rejecting the undesirable extreme version of identity politics. It is clear that the narrow conceptualization of identity politics within the contexts of race and religion may impede the promotion of other identities such as gender and the marginalize. However, a less extreme and positive version of identity politics can promote beneficial and needed social, political, and other changes if framed in a more positive way. Some of the characteristics of a more positive politics of identity include the focus on seeking to improve welfare of the discriminated, marginalized, neglected and/or oppressed groups using non-violence and non-confrontational approach, focusing on similarities and commonalities between opposing groups or identities instead of division and hatred, conceptualization of identity politics beyond communal politics and finally promoting instead of stifling dialogue or conversation in the name of political correctness.